Design of dispersion-engineered As 2 Se 3 channel waveguide for mid-infrared region supercontinuum generation - Karim, Mohammad Rezaul; Ahmad, Harith; Ghosh, Souvik; Rahman, B.M. Azizur (AIP Publishing, 2018)
In recent years, low cost and scalable integrated optics compatible planar waveguides have emerged for an ultrabroadband supercontinuum generation between ultraviolet and mid-infrared region applications. A 20-mm-long integrated photonics compatible highly nonlinear As 2 Se 3 channel waveguide, which exhibited wider as well as lower magnitude and nearly flat anomalous dispersion region, designed and modeled by employing GeAsSe glass for its upper and lower claddings. Using pump source at 6 μm with a pulse duration of 170-fs, an ultrabroadband long wavelength region supercontinuum broadening covering the wavelength from 3.5 μm to 15 μm could be predicted with the largest input peak power of 10 kW. Increasing the power further to 20 kW does not enhance the supercontinuum expansion noticeably beyond 15 μm. This numerical demonstration could be the longest supercontinuum generation by an on-chip integrated photonics compatible planar waveguide which can be used for a variety of mid-infrared region applications.